Visualizing Diffusion Tensor MR Images Using Streamtubes and Streamsurfaces - Zhang, Song; Curry, Charlie; Morris, Dan; Laidlaw, David H (Human Brain Project Annual Meeting, 2000, 2000)
In biological tissue, water is ubiquitous and constantly in motion. This motion of water inside biological tissue is called diffusion. Water usually diffuses at different rates both in different locations and along different directions at one location. The difference of diffusion rates at one location is called anisotropy. The following pictures show three types of diffusion illustrated by the ellipsoids. The ellipsoid would be regarded as the shape that the water will diffuse into from one point after a short period of time. Thus it is a natural icon for diffusion information. The diffusion of water is constrained by, and correlated with, micro-structure in the biological tissue. By visualizing diffusion information, we can elucidate the connectivity and micro-structural detail. With MRI technology, diffusion information can be measured in vivo from biological tissues, producing a three-dimensional, second-order tensor field. This tensor field consists of a description of the diffusion information at every sample point in the three-dimensional volume. In this project, we produce images from the three-dimensional diffusion tensor fields that illustrate the connectivity and other micro-structural information in the nervous system; we provide the user with interactivity so that he/she can explore the image from different angles and distances; we also put anatomical landmarks in the image which is proved to be essential in understanding the images.